Medication adherence in heart failure with preserved ejection fraction: Impact on quality of life after one year (Research, Society and Development, 2025)
Introduction: Heart failure with preserved ejection fraction (HFpEF) accounts for more than 50% of prevalent heart failure (HF) cases worldwide. The pathophysiology of this condition is not yet fully understood, and the lack of consensus regarding therapeutic approaches and clinical outcome assessment creates a significant gap, requiring further research to develop more effective and targeted treatment strategies. Objective: To evaluate the relationship between medication adherence and quality of life in patients with HFpEF diagnosed for more than one year. Methods: This is a retrospective cohort study including patients with an HFpEF diagnosis for over one year who were in outpatient follow-up. Patients underwent a consultation to assess medication adherence and quality of life. Medication adherence was evaluated using the Morisky Medication Adherence Scale (MMAS-8), while quality of life was assessed using the Minnesota Living with Heart Failure Questionnaire (MLHFQ). In case of an event, patients provided hospital documentation for evaluation. Conclusion: The findings of this retrospective cohort study contribute to expanding the understanding of HFpEF, especially with regard to the relationship between medication adherence and quality of life. Although adherence to treatment is a central element in the management of HF, our results indicate that, in HFpEF, quality of life is influenced by multiple factors, including clinical conditions, comorbidities and socioeconomic characteristics.